Frequency and predictors of suboptimal glycemic control in an African diabetic population - Kibirige, Davis; Akabwai, George Patrick; Kampiire, Leaticia; Kiggundu, Daniel Ssekikubo; Lumu, William (International journal of general medicine, 2017)
Persistent suboptimal glycemic control is invariably associated with onset and progression of acute and chronic diabetic complications in diabetic patients. In Uganda, studies documenting the magnitude and predictors of suboptimal glycemic control in adult ambulatory diabetic patients are limited. This study aimed at determining the frequency and predictors of suboptimal glycemic control in adult diabetic patients attending three urban outpatient diabetic clinics in Uganda.
Keywords: suboptimal glycemic control; frequency; predictors